PENGARUH PERSEPSI WAJIB PAJAK ATAS PENERAPAN PERATURAN PEMERINTAH NO. 23 TAHUN 2018, PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL, DAN MENENGAH KOTA MALANG - Rizki Dwi Prasetyo Sunaryo; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study was to determine the effect of perception of taxpayers on the application of Government Regulation no. 23 of 2018, Taxation Understanding and Taxpayer Awareness of Micro, Small and Medium Business Taxpayer Compliance in Malang City. Samples were selected using purposive sampling obtained by 240 respondents based on the criteria applied. This research uses multiple linear regression models. The results of this study indicate that the Perception of Taxpayers on the Application of Government Regulation No. 23 of 2018, Taxpayer Understanding and Taxpayer Awareness has a significant positive effect on Taxpayer Compliance No. 23 of 2018. Perception of Taxpayers on the Application of Government Regulation No. 23 of 2018 does not affect the compliance of Micro, Small and Medium Enterprises Taxpayer Malang. Understanding Taxation has a significant positive effect on Compliance of Micro, Small and Medium Enterprises Taxpayer Malang. Awareness of Taxpayers has a significant positive effect on compliance of Micro, Small and Medium Business Taxpayers of Malang City.Keywords: Perception of Taxpayers on the Application of Government Regulation No. 23 of 2018, Understanding of Taxation and Taxpayer Awareness and Taxpayer Compliance